2014
DOI: 10.1007/s10886-014-0488-z
|View full text |Cite
|
Sign up to set email alerts
|

Field Evaluation of the Bacterial Volatile Derivative 3-Pentanol in Priming for Induced Resistance in Pepper

Abstract: Plants are defended from attack by emission of volatile organic compounds (VOCs) that can act directly against pathogens and herbivores or indirectly by recruiting natural enemies of herbivores. However, microbial VOC have been less investigated as potential triggers of plant systemic defense responses against pathogens in the field. Bacillus amyloliquefaciens strain IN937a, a plant growth-promoting rhizobacterium that colonizes plant tissues, stimulates induced systemic resistance (ISR) via its emission of VO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(60 citation statements)
references
References 52 publications
4
55
0
1
Order By: Relevance
“…3-Pentanol application protected pepper in the field from X. axonopodis pv. vesicatoria and Cucumber mosaic virus associated with primed expression of defense genes in the JA and SA pathways after infection (17). Similarly, Arabidopsis recognizes the bacterial T lymphocytes (T cells): a lymphocyte (a type of white blood cell) important to cell-mediated immunity B lymphocyte (B cell): a type of white blood cell in macromoleculemediated (humoral) immunity of the mammalian adaptive immune system Natural killer (NK) cells: a cytotoxic lymphocyte (a type of white blood cell) in the mammalian innate immune system Monocytes: white blood cells in the innate mammalian immune system; produce multiple defensive substances (e.g., interleukins) Macrophages: cells important to mammalian immunity; produce multiple defensive substances (e.g., interleukins) Cytokine: small protein important to mammalian cell signaling quorum sensing molecule N-acyl-homoserine lactone to prime cell wall-associated defense (callose deposition, accumulation of phenolics, lignification) associated with immunity to P. syringae (110).…”
Section: Priming By Beneficial Microbesmentioning
confidence: 99%
“…3-Pentanol application protected pepper in the field from X. axonopodis pv. vesicatoria and Cucumber mosaic virus associated with primed expression of defense genes in the JA and SA pathways after infection (17). Similarly, Arabidopsis recognizes the bacterial T lymphocytes (T cells): a lymphocyte (a type of white blood cell) important to cell-mediated immunity B lymphocyte (B cell): a type of white blood cell in macromoleculemediated (humoral) immunity of the mammalian adaptive immune system Natural killer (NK) cells: a cytotoxic lymphocyte (a type of white blood cell) in the mammalian innate immune system Monocytes: white blood cells in the innate mammalian immune system; produce multiple defensive substances (e.g., interleukins) Macrophages: cells important to mammalian immunity; produce multiple defensive substances (e.g., interleukins) Cytokine: small protein important to mammalian cell signaling quorum sensing molecule N-acyl-homoserine lactone to prime cell wall-associated defense (callose deposition, accumulation of phenolics, lignification) associated with immunity to P. syringae (110).…”
Section: Priming By Beneficial Microbesmentioning
confidence: 99%
“…Application of this compound as soil drench induced ISR in tobacco and corn respectively against B. cinerea and Cochliobolus heterostrophus. Choi and collaborators also recently reported that the 3-pentanol produced by B. amyloliquefaciens IN937a stimulate ISR in pepper against Xanthomonas axonopodis and Cucumber mosaic virus (Choi, Song, Yi, & Ryu, 2014).…”
Section: Volatilesmentioning
confidence: 92%
“…isolated from soil; 1-pentanol strongly reduced phytopathogen infection in pepper (data not shown). The derivative 3-pentanol alleviated the pepper disease severity caused by X. axonopodis and naturally occurring Cucumber mosaic virus, and RT-PCR analysis showed that pentanol elevated the expression of defense-related genes involved in SA, JA, and ET signaling pathways (including Pathogenesis-related genes) (Choi et al 2014). Therefore, pentanol and its derivatives have potential as candidate bioprotectants.…”
Section: Pentanol and Its Derivativesmentioning
confidence: 99%
“…Indole promotes Arabidopsis growth and has a crucial role in lateral (Zou et al 2010;Velázquez-Becerra et al 2010;Meldau et al 2013;Bailly et al 2014); tridecane, 3-petanol, and 1-octen-3-ol function as bioprotectants (Gutiérrez-Luna et al 2010;Lee et al 2012;Huang et al 2012;Choi et al 2014;Erb et al 2015) root growth, which can be mediated by disrupting the auxinsignaling machinery (Bailly et al 2014). Recent work used the auxin reporter DR5::GUS lines and classic auxin physiological and transport assays to show that plants can convert bacterial indole to auxin (indole acetic acid), and the polar auxin transport machinery is crucial for indole-induced lateral root growth.…”
Section: Indolementioning
confidence: 99%
See 1 more Smart Citation